A Framework for Effective Bt Maize IRM Programs: Incorporation of Lessons Learned From Busseola fusca Resistance Development - Bouwer, Gustav (Frontiers in Bioengineering and Biotechnology, 2020)
Bt maize is genetically engineered to express insecticidal proteins from the bacterium Bacillus thuringiensis. Bt maize is used extensively by South African farmers to reduce yield losses caused by lepidopteran larvae. Starting in the 2004/2005 season, severe Busseola fusca-associated damage to Cry1Ab-expressing Bt maize was noted by South African farmers. The unsatisfactory pest control was eventually attributed to the development of insect resistance to the Cry1Ab protein in the Bt maize hybrids. An assessment of the historical events surrounding the development of resistance by B. fusca showed that there was room for improvement both in the insect resistance management (IRM) strategy selected and the implementation of the strategy. With the recent arrival of fall armyworm (Spodoptera frugiperda) in Africa, it is important to have IRM programs that are appropriate for all of the pests that constitute the maize lepidopteran pest complex. After identification of shortcomings in the IRM programs implemented in South Africa, a framework is proposed for effective Bt maize IRM programs. The IRM framework integrates pre-marketing research, post-marketing monitoring, and two-level remedial action plans. The core of the framework is a regulator-approved IRM strategy that is based on comprehensive pre-marketing research and serves to guide stakeholders during the post-marketing phase. The framework will assist technology developers and regulators, especially those with nascent regulatory systems, to select and implement IRM strategies that facilitate sustainable pest management.